Sex, organal and seasonal differences of Belminthofauna of toad, bufo melanostictus (Schneider, 1799) (Bangladesh Journal of Zoology, 2013)
A total of 75 toads (39 males and 36 females), Bufo melanostictus, collected from different areas of Dhaka city from May 2009 to April 2010 was examined for helminth parasites. The results showed that seven parasite species were collected, and prevalence of infection was 100%. The parasite fauna was comprised of Trematoda: 8% was the prevalence of Ganeo kumaonensis, 8% of Halipegus eccentricus; Nematoda: 100% of Oswaldocruzia indica, 68% of Neopharyngodon sp., 40% of Rhabdias bufonis; Acanthocephala: 28% of Pseudoacanthocephalus bufonis; and Pentastomida: 4% of Raillietiella indica. Serious damage was observed in intestine (53.94%) then rectum (24.55%), stomach (12.73%) and lungs (8.78%). The males had a higher intensity (77.92) than the females (44.58). Seasonally, the highest intensity of infection was found in the rainy season (81.21) and lowest during the winter (39.87). DOI: http://dx.doi.org/10.3329/bjz.v40i2.14308 Bangladesh J. Zool. 40(2): 155-164, 2012